Breastfeeding duration in infancy and dietary intake in childhood and adolescence. (1st March 2021) - Kheir, Fatima; Feeley, Nancy; Maximova, Katerina; Drapeau, Vicky; Henderson, Mélanie; Van Hulst, Andraea
Abstract: Although several studies have focused on associations between breastfeeding and child obesity, few have focused on associations with dietary intake. We examined associations between breastfeeding duration in infancy and dietary intake in childhood and explored whether associations are still observed in adolescence. The QUALITY (QUebec Adipose and Lifestyle InvesTigation in Youth) cohort includes 630 children aged 8–10 years at baseline (T1) who have at least one parent with obesity. A follow-up assessment was done 7 years later (T2) when participants were aged 15–17 years (n=377). Non-exclusive breastfeeding duration was evaluated at T1 using a parent questionnaire (never, < 3 months, 3–6 months, > 6 months). Dietary intake was assessed at T1 and T2 using three 24-h diet recalls, namely daily servings of vegetables (≥ 2 vs < 2), fruits (≥ 2 vs < 2), vegetables and fruits combined (≥ 5 vs < 5), sugar-sweetened beverages (SSB) (none vs any), and an overall diet quality index (DQI-I) (good vs poor). Multiple logistic regressions, adjusted for age, sex and total kilocalorie intake of the child, for age and body mass index of the mother, and for parental education and income were used. Compared to children breastfed > 6 months (reference group), those never breastfed or breastfed for 3–6 months were 42% (OR = 0.58, 95% CI: 0.34–0.96) and 38% (OR = 0.62, 95% CI: 0.39–1.00) less likely to consume ≥ 2 servings of vegetables per day at 8–10 years, respectively, while no association was found for those breastfed < 3 months. Compared to children breastfed > 6 months, those never breastfed were 1.8 times more likely to drink any SSB (OR = 1.82, 95% CI: 1.03–3.22). No associations were found for other diet indicators, and associations observed in childhood were no longer found by adolescence. In this cohort, breastfeeding was associated with greater vegetable intake and the avoidance of SSB in childhood, but not in adolescence, nor were associations found for fruit intake or overall diet quality.